2014
DOI: 10.1103/physrevstab.17.110701
|View full text |Cite
|
Sign up to set email alerts
|

Terawatt x-ray free-electron-laser optimization by transverse electron distribution shaping

Abstract: We study the dependence of the peak power of a 1.5 Å Terawatt (TW), tapered x-ray free-electron laser (FEL) on the transverse electron density distribution. Multidimensional optimization schemes for TW hard x-ray free-electron lasers are applied to the cases of transversely uniform and parabolic electron beam distributions and compared to a Gaussian distribution. The optimizations are performed for a 200 m undulator and a resonant wavelength of λ r ¼ 1.5 Å using the fully three-dimensional FEL particle code GE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…The strength of the guiding (given by the electron beam refractive index [141]) is proportional to the beam bunching which underscores the importance of maintaining a large fraction of the beam trapped and bunched in the tapered wiggler for maximum output efficiency. Recent numerical studies have suggested improving the effect of the guiding by varying the electron beam spot-size in the tapered section [77] or shaping the electron transverse distribution from Gaussian to parabolic or uniform [100], yielding a relative improvement in the efficiency around 10-40%.…”
Section: Transverse Effectsmentioning
confidence: 99%
“…The strength of the guiding (given by the electron beam refractive index [141]) is proportional to the beam bunching which underscores the importance of maintaining a large fraction of the beam trapped and bunched in the tapered wiggler for maximum output efficiency. Recent numerical studies have suggested improving the effect of the guiding by varying the electron beam spot-size in the tapered section [77] or shaping the electron transverse distribution from Gaussian to parabolic or uniform [100], yielding a relative improvement in the efficiency around 10-40%.…”
Section: Transverse Effectsmentioning
confidence: 99%
“…Finally, we note that there is a strong demand in the FEL science community for higher photon flux per pulse, to reach the level needed for imaging large systems such as protein molecules [42]. These applications require peak powers in the multi-TW range, contained in 25-100 fs pulses, to permit imaging before the destruction of the target.…”
Section: Introductionmentioning
confidence: 99%
“…The drive laser strikes the photocathode surface to emit electrons. The temporal and transverse shape of the laser pulse, together with the quantum efficiency (QE) of the photocathode surface, determines the temporal and transverse distribution of the electron beam upon emission, which has a significant impact on beam brightness and FEL performance [5][6][7][8][9][10]. The temporal distribution can be manipulated with techniques such as polarization based pulse stacking with birefringent crystals [11], acousto-optic modulators [12,13] or spatial modulators at a dispersion region [14].…”
Section: Introductionmentioning
confidence: 99%